2018
DOI: 10.1021/acs.jproteome.8b00323
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycan Branching and Fucosylation Are Increased Directly in Hcc Tissue As Determined through in Situ Glycan Imaging

Abstract: Hepatocellular carcinoma (HCC) remains as the fifth most common cancer in the world and accounts for more than 700,000 deaths annually. Changes in serum glycosylation have long been associated with this cancer but the source of that material is unknown and direct glycan analysis of HCC tissues has been limited. Our laboratory previously developed a method of in situ tissue based N-linked glycan imaging that bypasses the need for microdissection and solubilization of tissue prior to analysis. We used this metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 58 publications
(105 reference statements)
3
62
0
Order By: Relevance
“…FlexImaging‐generated glycan images normalized to total ion current were then searched using accurate mass against a database of known glycans generated using GlycoWorkbench. Glycan structures annotated in this paper are compositionally accurate as determined by mass as well as prior structural characterizations by MALDI‐FTICR MS, or MALDI–time‐of‐flight mass spectrometry (MALDI‐TOF MS), and liquid chromatography‐MS/MS . A key to monosaccharide unit symbols used to construct depictions of glycan structures is provided in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…FlexImaging‐generated glycan images normalized to total ion current were then searched using accurate mass against a database of known glycans generated using GlycoWorkbench. Glycan structures annotated in this paper are compositionally accurate as determined by mass as well as prior structural characterizations by MALDI‐FTICR MS, or MALDI–time‐of‐flight mass spectrometry (MALDI‐TOF MS), and liquid chromatography‐MS/MS . A key to monosaccharide unit symbols used to construct depictions of glycan structures is provided in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…These glycans were found to be with increased levels of fucosylation and/or with increased levels of branching. They also found that increased levels of fucosylated glycoforms were associated with a reduction in survival time (West et al, ).…”
Section: Discovery—mass Spectrometry‐based Assaysmentioning
confidence: 97%
“…5,43 An increase in the fucosylation levels coupled with increasing levels of fucosylated glycoforms observed in the h most common cancer-hepatocellular carcinoma can be utilized for early detection of the disease. 44 The signicance of sialylation and sialylated glycans in breast cancer brain metastasis was studied. 45 Changes in glycosylation emerge due to the alteration in expression levels of glycosyltransferases in the Golgi compartment of tumor cells.…”
Section: Viral Pathogensmentioning
confidence: 99%